Sungai ayung yang mempesona I Ketut Madia ; penyunting Hermawan H. Nugroho ; ilustrasi Agus Sudariswanto - MADIA, I Ketut, 1960; Nugroho, Hermawan H.; Sudariswanto, Agus (2001)
viii, 101 hlm ilus 20 cm